Evaluation of Digital Dependence of Employees in the Organizational Environment - Lucio Lage Gonçalves; Antonio Egídio Nardi; Sandra Bortolanza; Mariana King; Hugo Santos; Douglas Rodrigues; Anna Lucia Spear King (SAGE Publishing, 2022)
Introduction : With the evolution of technologies, new digital resources have emerged establishing different practices in human behavior, including the excessive use of digital devices, causing different dependencies due to the nonconscious use of these technologies. The digital use of digital devices will always be very important to the organizational process, but the abusive or excessive use can bring performance problems at work and also for people. Collective environments of organizations also begin to show "symptoms" of these dependencies, and observing these behaviors can contribute to greater employees comfort and the functioning of the business organization. Objective : To identify the level of digital dependency of employees in organizational environments and to investigate this dependency associated with demographic characteristics. Method: Data collection took place online, from 11.05.2019 to 03.05.2020, with a sample totaling 307 volunteers and 13 questionnaires excluded due to filling error, ending with 294 valid questionnaires. A validated scale was used to Assess Digital Employee Dependence (EDDE), with 19 questions (Annex 1) and inserted in the Google Forms platform, widely used for data collection in surveys. After the collection procedure, a database was created for statistical analysis and discussion of the results. Results : Factor Analysis identified 4 factors using the Kaiser Method, via Scree Plot and 19 questions were maintained, according to previous applications of this questionnaire. The sample presented itself without digital dependence (42.2%) or with mild dependence (30.3%). Only women had a severe level of digital dependence, but with low significance (1.7%). Conclusion : The severe digital dependency had a very low score, while the sum of volunteers without dependence with a mild level characterizes a sample without relevant digital dependence. Women showed a higher level of digital dependence although more research needs to confirm this sign. The limitations found for applying the research did not compromise the results.